Urbanisation reduced body size but potentially improved flight performance in bees and wasps - Ferrari, Andrea; Tommasi, Nicola; Polidori, Carlo (Basic and applied ecology, 2024)
Urbanisation is a main driver of land-use change, leading to rising in temperatures and fragmentation and reduction of green areas. Bees and wasps, which are important insect groups due to the ecosystem services they provide, may respond to this disturbance via changes in morphological traits which are functionally relevant. To date, studies focusing on this aspect only investigated few social bee species, and often gave contrasting results even at intra-generic level. Here, we studied how body size, wing loading, wing aspect ratio and wing fluctuating asymmetry vary in a social ground-nesting bee (Halictus scabiosae), a solitary hole-nesting bee (Osmia cornuta) and a social paper wasp (Polistes dominula) along an urbanisation gradient within Milan (Italy). By assessing the effects of temperature, green areas fragmentation and vegetation productivity on the above-listed functional traits, we found the three species to variably respond to increasing urbanisation, albeit the driving environmental parameters differed among species. More specifically, smaller individuals were sampled in warmer (for bees) and in less productive (for wasps) areas along the urbanisation gradient. Furthermore, greater wing aspect ratio values were recorded at warmer locations for H. scabiosae, lower wing loading was recorded at more fragmented sites for O. cornuta, and greater wing loading was recorded at locations with greater productivity for P. dominula. H. scabiosae and P. dominula showed greater wing fluctuating asymmetry at more fragmented sites. Although distinct species seemed sensitive to different driving factors, our results point toward a consistent response: smaller body but potentially improved flight performance in more urbanised environments.